Limiting the Risk of Osteoarthritis After Anterior Cruciate Ligament Injury: Are Health Care Providers Missing the Opportunity to Intervene?. Issue 12 (19th October 2021) - Davis, Aileen M.; Chahal, Jas; Wong, Rosalind; Steinhart, Krista; Dwyer, Tim; Li, Linda; Marks, Paul; Cruz, Laura; Urquhart, Nathan; Wilson, Janie Astephen; Cudmore, David; Nimmon, Laura; et al.
Abstract : Objective: To understand what sports orthopedic surgeons (OS), primary care physicians (PCPs) with sports medicine training, and physical therapists (PTs) managing nonelite athletes with anterior cruciate ligament (ACL) injury tell their patients about their osteoarthritis (OA) risk. Methods: An electronic survey was distributed by the Canadian Academy of Sport and Exercise Medicine (PCPs, OS), the Sports and Orthopedic Divisions of the Canadian Physiotherapy Association (PTs), and to OS identified through the Royal College of Physicians and Surgeons and the Canadian Orthopaedic Association. The survey included 4 sections: demographics, factors discussed, timing of discussions, and discussion of risk factors and their management. Proportions or means with 95% confidence intervals were calculated. Results: A total of 501 health care professionals (HCPs) responded (98 PCPs, 263 PTs, and 140 OS). Of those responding, 70–77% of physicians reported always discussing OA risk, but only 35% of PTs did. All HCPs reported that patient activities perceived as detrimental to knee health, ACL reinjury, and simultaneous injury to other structures in the knee were most often the reason for discussing OA risk. OA risk was discussed at initial management post‐injury (65–94%), with few discussing risk subsequently. Eighty percent of physicians and 99% of PTs indicated that PTs were suited to provide OA risk and management information. Conclusion: HCPs routinely managing people with ACL injury do not consistently discuss OA risk post‐injury with them. Educational strategies for HCPs are urgently needed to develop care pathways inclusive of support for OA risk management following ACL injury.